2016
DOI: 10.1038/cddiscovery.2016.61
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of intramyocellular lipid accumulation by lipophagy and a p62-mediated pathway

Abstract: We have previously observed the reversal of lipid droplet deposition in skeletal muscle of morbidly obese patients following bariatric surgery. We now investigated whether activation of autophagy is the mechanism underlying this observation. For this purpose, we incubated rat L6 myocytes over a period of 6 days with long-chain fatty acids (an equimolar, 1.0 mM, mixture of oleate and palmitate in the incubation medium). At day 6, the autophagic inhibitor (bafilomycin A1, 200 nM) and the autophagic activator (ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 33 publications
5
40
2
Order By: Relevance
“…The reciprocal relationship between LDs and autophagy was first described by Singh et al . where they showed that the presence of exogenous lipids leads to inhibition of autophagy and accumulation of triglycerides promoting lipotoxic‐mediated cell death . This is in contrast to what we observed in our study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The reciprocal relationship between LDs and autophagy was first described by Singh et al . where they showed that the presence of exogenous lipids leads to inhibition of autophagy and accumulation of triglycerides promoting lipotoxic‐mediated cell death . This is in contrast to what we observed in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…Another report highlighted the role of ATGL‐mediated LD catabolism in the liver that involved SIRT1 as the primary mechanism for lipophagy and fatty acid oxidation . Pertinent to our observation, a recent study highlighted the role of p62/SQSTM1 in promoting lipophagy by binding to ADRP on the LD . In our study, we showed that p62/SQSTM1 interacts with cPLA2 and LC3B on LDs.…”
Section: Discussionsupporting
confidence: 88%
“…A separate study reveals rapamycin-driven autophagy promotes localization of p62 on lipid droplets via interaction with perilipin 2 (PLIN2), a lipid droplet membrane protein. The recruitment of p62 to lipid droplets decreases lipid accumulation in myocytes efficiently, suggesting that p62 may direct autophagosomes to the lipid droplets and accelerate lipid turnover by lipophagy [18]. Interestingly, mutations in the protein huntingtin which associates with organelle membranes lead to accumulation of dysfunctional autophagosomes as well as cytoplasmic lipid droplets in multiple cell types [19].…”
Section: Molecular Machinery Of Lipophagy: Identification and Inductionmentioning
confidence: 99%
“…As the liver is a primary tissue controlling both gluconeogenesis and ketogenesis and starvation is a powerful autophagy inducer in the liver and muscle as well, it is plausible to speculate that muscle autophagy could directly impact the liver or vice versa . Although defective autophagy in the muscle causes accumulation of intramyocellular triglycerides and enhanced autophagy facilitates removal of lipids from muscle cells (28), Takagi et al recently demonstrated in tissue-specific ATG5 knockout mice that the mice lacking ATG5 in both the liver and muscle indeed exhibited the improvement of metabolic profile, as compared to liver-specific knockout counterparts, suggesting that autophagy in the skeletal muscle may be metabolically distinct from that in the liver (46). In an independent study, skeletal muscle–specific ATG7 knockout mice also showed lower lipid accumulation and higher expression of β-oxidation–related genes, as compared to control mice (26).…”
Section: Effects Of Muscle Autophagy On the Livermentioning
confidence: 99%